Ovarian transcriptome analysis of diploid and triploid rainbow trout revealed new pathways related to gonadal development and fertility - J. Nynca; M. Słowińska; J. Wiśniewska; J. Jastrzębski; S. Dobosz; A. Ciereszko (Animal, 2022)
Triploidisation represents several advantages (e.g. sterility) and therefore is routinely applied in aquaculture of several commercially important fish species, including rainbow trout. The comparative transcriptomic analysis of ovaries of triploid (3N) and diploid (2N) female rainbow trout revealed a total of 9 075 differentially expressed genes (DEGs; 4 105 genes upregulated in 2N and 4 970 genes upregulated in 3N ovaries, respectively). Identified clusters for DEGs upregulated in 3N and 2N ovaries were different, including carbohydrate and lipid metabolic process and transport, protein modification, signalling (related to folliculogenesis) and response to stimulus for DEGs upregulated in 2N, and developmental process, signalling (related to apoptosis, cellular senescence and adherence junctions) and regulation of RNA metabolic process for DEGs upregulated in 3N. The enrichment of processes involved in carbohydrate and lipid metabolism in 2N ovaries indicated high metabolism of ovarian tissue and the energy reservoir generation indispensable during the earliest stages of development. Our results highlight the importance of oocyte hydration along with oestrogen, insulin, leptin, fibroblast growth factor, and Notch signalling and pathways related to the regulation of cyclic adenosine monophosphate (cAMP) levels in proper oocyte meiotic maturation prior to ovulation in 2N ovaries. Conversely, triploidisation may lead to an increase in ovarian cellular senescence and apoptosis, which in turn can result in abnormal gonadal morphology and fibrosis. The downregulation of genes responsible for the precise regulation of meiosis and proper chromosome segregation during meiosis probably affects meiotic maturation via irregular meiotic division of chromosomes. The induction of triploidy of the rainbow trout genome resulted in enhanced expression of male-specific genes, genes responsible for re-establishing the transcriptional balance after genome reorganisation and genes involved in regulatory mechanisms, including gene silencing and DNA methylation. To the best of our knowledge, this is the first genome-wide investigation providing in-depth comprehensive and comparative gene expression patterns in the ovary from 2N and 3N rainbow trout females helping in elucidating the molecular mechanisms leading to impaired gonadal development and sterility of female triploids.